2011
DOI: 10.1021/la104195v
|View full text |Cite
|
Sign up to set email alerts
|

A Facile in Situ Hydrothermal Method to SrTiO3/TiO2 Nanofiber Heterostructures with High Photocatalytic Activity

Abstract: Heterostructured SrTiO3/TiO2 nanofibers were fabricated by in situ hydrothermal method using TiO2 nanofibers as both template and reactant. The as-fabricated heterostructures composite included SrTiO3 nanocubes or nanoparticles assembled uniformly on the surface of TiO2 nanofibers. Compared with the pure TiO2 nanofibers, SrTiO3/TiO2 nanofibers exhibited enhanced photocatalytic activity in the decomposition of Rhodamine B (RB) under ultraviolet light. The enhanced photocatalytic activity of SrTiO3/TiO2 nanofibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(170 citation statements)
references
References 34 publications
8
161
0
1
Order By: Relevance
“…2b, the spectrum of Ti 2p can be separated into three peaks at about 458.3, 464.0 and 472.1 eV. According to the references, 31,32 the previous two peaks were respectively attributed to Ti 2p 3/2 and Ti 2p 1/2 of the TNTs, and the last at 472.1 eV was depicted as Ti 2p 3/2 of SrTiO 3 . Two peaks of O 1s centered at approximately 529.6 and 531.8 eV could be observed in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…2b, the spectrum of Ti 2p can be separated into three peaks at about 458.3, 464.0 and 472.1 eV. According to the references, 31,32 the previous two peaks were respectively attributed to Ti 2p 3/2 and Ti 2p 1/2 of the TNTs, and the last at 472.1 eV was depicted as Ti 2p 3/2 of SrTiO 3 . Two peaks of O 1s centered at approximately 529.6 and 531.8 eV could be observed in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…MWCNTs as support provides mechanical integrity to the support structure, whereas titania nanowires are proven to be active towards catalysis [52,53]. Literature report also shows titania in nanowire/nanorod form to be catalytically more active than in spherical form [33]. The MWCNTs in the interconnected twinned-structure also act as charge-carriers and compensate for the conductivity loss with titania.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al reported that titania nanotubes prepared from polycrystalline TiO 2 have more interesting and unique properties than the latter [32]. It has been reported that the one-dimensional TiO 2 has larger surface area than the TiO 2 nanoparticles, which is essential, particularly in heterogeneous catalysis [32][33][34]. Shen et al investigated TiO 2 /MWCNTs based nanocomposites for usage in lithium-ion battery and this nanocomposite seems to be ideal for fast and efficient lithium storage [35].…”
Section: Introductionmentioning
confidence: 99%
“…With the steady and fast growing field of nanoscience and nanotechnology, nanostructured ceramics like zinc oxide and titanium oxide has become a promising photocatalyst for its high catalytic activity, low cost, and environmental friendliness [50,51,55,57, Electrospinning ceramic nanofibers have extremely high surface area due to its small sizes, and further provide channels for quick charge transfer due to its 1D nanostructures. Therefore, electrospun ceramics have huge potential for photo catalyst applications [47,57,[145][146][147][148][149][150][151][152][153][154][155]. Our group fabricated photocatalytically active Ag-ZnO composite nanofibers by electrospinning (Fig.…”
Section: Photo Catalystmentioning
confidence: 99%